Technology Platforms in the Russian Innovation Policy Practice - Pavel Rudnik (Foresight and STI Governance)
Technology platforms are regarded as an important tool for linking disparate elements of the innovation system and shaping an integrated innovation framework. Platforms can be a part of the institutional framework for building relationships along one of the axes of the innovation system “universities – research organizations – industry” and provide a basis for the elaboration and implementation of focused and comprehensive innovation policy in different areas.